Distribution and preliminary conservation assessments of commonly used forest species in the Nepalese Himalayas - Adhikari, B; Pendry, C. A.; Måren, I. E.; Bhattarai, K. R.; Chaudhary, R. P. (Banko Janakari, 2017)
Balancing the trade-offs between biodiversity conservation and ecosystem service delivery is a colossal challenge in the areas of the globe with high productivity and high demand, such as in south Asia. In order to meet this challenge, we need enhanced knowledge of the species constituting these semi-natural systems. This paper reports the country-level preliminary conservation assessments for 153 woody plant species from the Middle Hills in central Nepal based on the IUCN criteria. Distribution maps and threat categories are provided for all species. Ten species are categorized as Near Threatened, two as Endangered and one as Vulnerable. Conservation assessments could not be completed for 24 species because of insufficient distribution data. Banko Janakari, Vol. 27, No. 1, Page: 43-54